DETERMINATION OF RESONANT ELECTRICAL CIRCUIT PARAMETERS BASED ON RESONANT FREQUENCY AND QUALITY FACTOR MEASUREMENTS - A.V. Svetlov (Penza State University Publishing House, 2021)
Background. The aim of the article is to develop a methodology to determine parameters of three-element resonant electric circuits based on resonant frequency and quality factor measurements. Materials and methods. The proposed technique provides for the measurement of resonant frequency, quality factor, and maximum voltage at the output of a measuring circuit with subsequent solution of a system of equations connecting the measured parameters with inductance, capacitance, and active resistance of the electrical circuit. Results. Calculated ratios are given, and an example of determining the parameters of a specific three-element resonant electric circuit, and estimating the error component due to imperfection of an operational amplifier, with a measuring circuit built thereon, is considered. Conclusions. An application of the proposed technique to determine the parameters of resonant electrical circuits based on resonant frequency and quality factor measurements made it possible to get rid of errors in analogue conversions of the output voltage of the measuring circuit. According to the simulation results, the error component does not exceed 1 % due to imperfection of the element base of the measuring circuit.